Efektivitas Kegiatan Kelompok Kerja Kepala Sekolah dalam Meningkatkan Kinerja Kepala Sekolah SD Negeri 244 Palembang - Asri Agustini; Nur Ahyani; Pahlawan Pahlawan (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2026)
This study aims to examine the effectiveness of the Principal Working Group activities in improving the performance of principals at SD Negeri 244 Palembang. The Working Group activities serve as a platform for principals to share experiences, broaden their insights, and develop their professional competencies. The research employs a descriptive method with both qualitative and quantitative approaches. Data were collected through observations, interviews, and questionnaires distributed to the principals who are members of the Working Group. The results indicate that active participation in these activities significantly contributes to enhancing managerial skills, leadership, and decision-making abilities of the principals. Furthermore, these activities foster effective communication and collaboration among principals, which positively impact the overall quality of the schools. Constraints such as limited time and resources were identified but can be minimized with better planning. In conclusion, the Principal Working Group activities are effective in improving the performance of principals at SD Negeri 244 Palembang, and it is recommended that these activities be continuously supported and developed as a means of enhancing principal professionalism.